The Loch Ness punster - Klise, Kate.; Klise, M. Sarah (Boston ; New York : Houghton Mifflin Harcourt, 2015)
Twelve-year-old Seymour Hope and his ghostly "mother" Olive go to Scotland to claim a castle inherited from Ignatius Grumply's punster uncle, Ian, but while they tend an aged tortoise and face an unscrupulous developer, Iggie deals with Ian's ghost and an inept insurance agent.
Keywords: Letters -- Fiction; Ghosts -- Fiction; Uncles -- Fiction; Inheritance and succession -- Fiction; Turtles -- Fiction; Scotland -- Fiction; Humorous stories; Letters -- Juvenile fiction; Ghost stories; Uncles -- Juvenile fiction; Inheritance and succession -- Juvenile fiction; Turtles -- Juvenile fiction; Scotland -- Juvenile fiction